Peran Museum Daerah Deli Serdang dalam Melestarikan Peninggalan Kesultanan Serdang - Murbarani, Febri; Naldo, Jufri; Purwaningtyas, Franindya (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
The museum is an institution that preserves historical objects for conservation and preservation purposes. The Museum Daerah Deli Serdang plays a role in preserving historical relics, one of which is the legacy of the Serdang Sultanate. This study aims to examine how the Museum Daerah Deli Serdang preserves the historical heritage of the Serdang Sultanate. The research employs a qualitative approach and descriptive method by conducting direct observation of the research object and documenting the findings as they occur at the research site. The results obtained from this study indicate that the museum's role can be described as an institution that collects, records, preserves, and conserves cultural heritage objects. The Museum Daerah Deli Serdang role in preserving the legacy of the Serdang Sultanate involves various activities such as acquiring collections, participating in events organized by the Serdang Sultanate family, and organizing public events such as museum learning sessions, collection reviews, and others. To preserve the legacy of the Serdang Sultanate, the Museum undertakes conservation efforts including maintenance, protection, restoration, development, and utilization.